Implementation Of Publik Service Using A whole Of Goverment Appoach At the Publik Service Mall Of Bengkulu City: Penyelenggaraan Pelayanan Publik Dengan Pendekatan Whole Of Government Di Mall Pelayanan Publik Kota Bengkulu - Ririn Anggriyani; Harmiati Harmiati; Heru Purnawan (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
According to the 2024 Ministry of Administrative and Bureaucratic Reform (KemenPAN-RB), Bengkulu City has not yet been recognized as a prime public service mall at the district/city level. Therefore, it can be concluded that public services in Bengkulu City are not yet categorized as the best compared to other cities. This study used a qualitative approach with descriptive methods. Data were collected through interviews with informants selected through purposive sampling, based on specific considerations regarding relevance to the research topic. Data were also obtained through direct observation and documentation. In analyzing the findings, this study referred to the theory proposed by Perry (6), which contains three main components: coordination, integration, and closeness and involvement. This study used a qualitative approach with descriptive research. The data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of public services using the Whole of Government approach at the Bengkulu City Public Service Mall has not been implemented properly. This can be seen from the factors that determine the success of the Whole of Government Approach, namely coordination, integration, closeness, and involvement. The coordination variable at the Bengkulu City Public Service Mall only creates coordination between government and non-government agencies, and the coordination established is limited to the establishment and operation of the Public Service Mall. In terms of integration, the implementation of public services in Bengkulu City has not yet achieved the MPP's goal of facilitating the completion of administrative matters within a single MPP building. Furthermore, the Closeness and Involvement variables established at the Bengkulu City Public Service Mall have not been achieved, as evidenced by the unclear organizational structure of the Bengkulu City MPP.